Penggunaan Kata â€œJancukâ€ Sebagai Ekspresi Budaya dalam Perilaku Komunikasi Arek di Kampung Kota Surabaya - Sriyanto, Sugeng; Fauzie, Akhmad (Jurnal Psikologi Teori dan Terapan, 2017)
The term â€œjancukâ€ is part of the dialect of Surabaya people. For Surabaya people known as â€œArek Suroboyoâ€ who lives in the neighborhood of kampung kota (the urban village), â€œjancukâ€ is the most common word that is used as an expressive language in daily life. However for some people, the word â€œjancukâ€ has a negative connotation. This ethnographic study explore how â€œjancukâ€ is used and understood by people living in kampung Surabaya who use it as daily communication. Data collected using in-depth interviews and analyzed using three stages of analysis technique suggested by Miles and Huberman: reduction, display, and verification. The result shows that the use of â€œjancukâ€ is the common expression in communication which is used because the influence of the social character and the strong internalization of â€œArekâ€ culture. â€œArekâ€ culture is characterized by its spontaneous, open, and egalitarian values. The use of â€œjancukâ€ emphasizes the form of interaction or pragmatic language functions rather than its semantic meaning. In general, the word â€œjancukâ€ is used by people who live in urban villages in Surabaya to express their emotion both positive and negative sides. While â€œjancukâ€ can be used to express anger, most participants used in friendship circle. People who use the word tend to be viewed as friendly and sociable.Abstrak: Bagi Arek Suroboyo yang tinggal di lingkungan kampung, kata â€œjancukâ€ digunakan sebagai sebagai bentuk ekspresi dalam kehidupan sehari-hari. Peneltian etnografi ini bertujuan untuk mengungkap bagaimana kata â€œjancukâ€ dimaknai oleh orang-orang yang menggunakannnya yang tinggal di kampung Surabaya. Data dikumpulkan melalui wawancara secara mendalam dan dianalisis menggunakan teknik reduksi, display, dan verifikasi yang disarankan Miles and Huberman. Hasil analisis menunjukkan Â penggunaan kata jancuk dalam perilaku komunikasi merupakan ekspresi yang dipengaruhi oleh karakter dan kuatnya internalisasi budaya â€œArekâ€. Budaya â€œArekâ€ ditandai oleh spontanitas, keterbukaan, dan egalitarianisme. Penggunaan kata jancuk lebih menekankan pada bentuk fungsi interaksi atau prakmatik bahasa dari pada makna semantiknya. Kata ini sering diucapkan oleh orang kampung Surabaya untuk mengekspresikan emosi positif maupun negatif. Menjadi negatif ketika kata ini digunakan sebagai ekspresi kemarahan yang ditujukan pada orang lain. Pada sisi positif dalam sebuah interaksi persahabatan, orang yang menggunakan kata iniÂ  dianggap Â memiliki karakteristik sebagai orang yang ramah dan suka bergaul.Â Â